Imperial Incarceration Detention without Trial in the Making of British Colonial Africa - Lobban, Michael (Social Sciences, 2021)
Michael Lobban examines the use of detention without trial in the British African Empire, evaluating the various legal powers used to facilitate imperial expansion. An essential text for lawyers and historians, Imperial Incarceration demonstrates the importance of context in understanding the law's effect.